2016
DOI: 10.1039/c6tc03624d
|View full text |Cite
|
Sign up to set email alerts
|

Achieving high-performance planar perovskite solar cells with co-sputtered Co-doping NiOxhole transport layers by efficient extraction and enhanced mobility

Abstract: Magnetron sputtered Co-doped NiO HTLs show greatly improved hole mobility and long-term stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 44 publications
4
66
0
Order By: Relevance
“…From the viewpoints of device stability and commercialization, inorganic HTMs are desired for continuous evolution of high‐performance PSCs . Various inorganic p‐type semiconductors with suitable optical properties, good stability, wide bandgaps, and matched energy levels such as CuSCN, NiO x , MoO 3 , and V 2 O 5 have been developed as efficient HTMs in PSCs …”
Section: Doped Htls In Planar Perovskite Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the viewpoints of device stability and commercialization, inorganic HTMs are desired for continuous evolution of high‐performance PSCs . Various inorganic p‐type semiconductors with suitable optical properties, good stability, wide bandgaps, and matched energy levels such as CuSCN, NiO x , MoO 3 , and V 2 O 5 have been developed as efficient HTMs in PSCs …”
Section: Doped Htls In Planar Perovskite Solar Cellsmentioning
confidence: 99%
“…Jin and co‐workers doped Co into NiO x HTL in p‐i‐n PSCs using magnetron sputtering deposition technique for the first time. The doped HTL shown an increased hole mobility and smoother surface morphology compared with the reference one.…”
Section: Doped Htls In Planar Perovskite Solar Cellsmentioning
confidence: 99%
“…Recently, Wei Chen et al reported Cs-doping in NiO x layers in inverted perovskites which facilitates deep valence band leading to an efficiency gain of 19.35% [55]. Similarly, doping of Co, Li-Cu, Cu, and Ag have also been reported [56][57][58][59].…”
Section: Reduction In Non-radiative Lossesmentioning
confidence: 99%
“…Thus far,s ophisticated and high-cost preparation methods such as pulsed laser deposition, high-temperature spray pyrolysis, and atomicl ayer deposition have been utilized to improve the qualityo ft he NiO film ascribed to high-performing solar cells, which are always reliant on the film's quality. [7,[10][11][12] Huang et al have demonstrated aP CE of 12.6 %f or ac obalt-doped NiO x solarc ell by the sputtering method; [13] whereas 16.4 %e fficiencyw as achieved when au niform NiO x layer was preparedt hrough the electrochemical deposition process. [11] The conductivity of NiO x is usuallyt uned by dopingw ith other elements such as copper, [14] cobalt, [13] or co-doping of lithium and cobalt [15] through stoichiometry adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…[7,[10][11][12] Huang et al have demonstrated aP CE of 12.6 %f or ac obalt-doped NiO x solarc ell by the sputtering method; [13] whereas 16.4 %e fficiencyw as achieved when au niform NiO x layer was preparedt hrough the electrochemical deposition process. [11] The conductivity of NiO x is usuallyt uned by dopingw ith other elements such as copper, [14] cobalt, [13] or co-doping of lithium and cobalt [15] through stoichiometry adjustment. By introducing copper as the co-dopant within the NiO x matrix, the PCE was dramatically increased from 8.9 %( foru ndoped NiO x )t oa ni mpressive efficiency of 15.4 %, revealing the effectiveness of the dopant in promoting the power conversion ability of the solar cell.…”
Section: Introductionmentioning
confidence: 99%